KAJIAN BIBLIKA WAHYU 11:1-13: KEDAULATAN ALLAH DALAM MELINDUNGI DAN MEMULIHKAN ORANG PERCAYA DARI PENDERITAAN : - - Moses Wibowo (Manna Rafflesia, 2025)
The rise of radicalism and violence in the name of religion in the digital era has caused suffering and fear, even threatening peaceful religious life. The church, as a community of believers, faces a great challenge in faithfully fulfilling its witness role amidst trials of faith. This research is grounded in the Christian belief that God remains sovereign in protecting and restoring believers in the context of suffering for their faith. The purpose of this study is to examine Revelation 11:1–13 as a biblical-theological foundation that affirms suffering is not a failure of faith, but part of the faithfulness in carrying out the mission of witness in the midst of life’s conflicts. The research method used is qualitative with a biblical interpretation approach through a structural exegesis model. The analysis shows that the two witnesses in Revelation 11 symbolize the church, which is called to proclaim God's truth, even at the risk of suffering. The conclusion affirms that God is not only sovereign eschatologically but also accompanies and restores His people. The novelty of this study lies in the contextual emphasis of Revelation 11:1–13 in responding to the crisis of religious violence and the affirmation that the church is called to be a faithful witness of Christ without retaliating violence with violence.